Company Releases Programmable, Versatile, Open Source Data Glove. - Paulson, Linda Dailey (Computer (00189162), 2010)
The article cites the latest programmable, and open source data glove developed by Anthrotronix company. It can function three ways, command and control games, robots, and other computer applications, it can communicate like in hand signals, and it can also do motion analysis like in sports training and physical therapy. It includes a software developer's kit to allow programmers to write applications for the glove using Java. Its initial cost of 649 U.S. dollars is cheaper compared to similar gloves, says Jack Vice, president of Anthrotronix.